Investigation of Imbalanced Activated Carbon Electrode Supercapacitors - Tieshi He; Xue Ren; Junping Nie; Jun Ying; Kedi Cai (International Journal of Electrochemistry)
Imbalanced supercapacitor was constructed by using various ratio of activated carbon (AC) of positive to negative electrode. The electrochemical behavior of imbalanced supercapacitor was investigated using 1.0 M spiro-(1,1′)-bipyrrolidinium tetrafluoroborate electrolyte in propylene carbonate. The results showed that there are some factors that influenced the imbalanced supercapacitor with different AC ratio of positive to negative electrode, the utilization of AC, electrode potential distribution, and life cycle. The imbalanced supercapacitor with an AC weight ratio of 80 : 120 of positive to negative electrode has an average potential distribution in each electrode, and it revealed the best electrochemical performance: specific capacitor was 39.6 F·g−1, while the charge-discharge efficiency was 97.2% after 2000 life cycle tests.